Effect of radio frequencies on the histological composition of nonsensory components of the teleost fishes eye - Tagreed Sabir; Ali Abid (College of Education for Pure Sciences, 2009)
Abstract The present study carried out to investigate the injuries of radio frequency on the nonsensory components (lens, cornea, choroid, iris, sclera and optic nerve) of two species of teleost fishes which were Chalcalburnus mussulensis and Noemacheilus angora. The fishes exposed to 80KHz and 1400 volts of radiofrequency for sixty day. The time of exposure was five hours daily. The dissection of samples occurred at thirty day and sixty day. The results revealed several histophathological changes for each of the above components, but the lesions were more sever in N.angora than C.mussulensis. After thirty day of exposure, different lesions were appeared in the various parts of the two species. The injuries were more sever at sixty day, which generally summarized as: lens cataract, pyknosis of lens capsule in C.mussulensis while in N.angora wide deterioration in lens was appeared which were pyknosis, necrosis and wrinkiling of the whole lens. The lesions of cornea were deterioration of some parts of central cornea epithelium, pyknosis of Bowmans membrane and keratocytes, degradation of Descemet membrane and endothelium. on the other hand necrosis and rarfaction of the stroma occurred: The previous lesions variable in the different regions of eye ball (dorsal, ventral etc.). The injuries were more sever in N.angora. The iris of C.mussulensis degenerate completely in some regions and appeared as a thin dens structure generally. In N.angora the iris dialated in some regions and several mass of melanocytes appeared in all of the area, necrosis of blood capillaries and gauanophore cells also appeared. In some regions the discrete feature of the iris disappeared. The choroid lesious in C.mussulensis appeared as: Necrosis and disruption blood capillaries, bleeding, necrosis rarefaction of the argentum layer, necrosis and shrinkage of choroid gland. In the N.angora most of the choroid was deteriorated. The sclera of the C.mussulensis showed rarefaction and unorganization of collagenous fibers at the central part, pyknosis and thining at the peripheral parts. In the N.angora rarefaction and swallowing of scleral collagenous fibers occurred. The optic nerve of the N.angora showed deterioration and edema in specific region. We could conclude that the low level of radiofrequency induced obvious and variable injuries in the nonsensory components of the eye of two species of fishes. The variation may be due to the species differences.